Sheet-shaped magnet for false eyelashes and method for manufacturing the same
Patent Information
- Application Number
- CN202610584653.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-04-29
AI Technical Summary
[0007]本发明的目的在于解决现有的假睫毛磁体存在的磁粉易团聚、韧性与耐汗性难以兼顾的问题
(1)本发明中对磁体粉末进行结构和性能改进,核壳结构钕铁硼粉末通过二氧化硅与生物基聚酯双层包覆,既可避免磁粉在基体中的团聚现象,使分散均匀度达95%以上,又能隔绝汗液中电解质的侵蚀,在37℃的人工汗液浸泡7天后,磁性衰减率≤1%,远优于现有的假睫毛磁体的衰减率,即说明本发明提供的假睫毛用片状磁体及其制备方案可显著延长假睫毛使用寿命。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of magnet technology, and more specifically, to a sheet magnet for false eyelashes and its preparation method. Background Technology
[0002] With the development of the beauty industry, magnetic false eyelashes have gradually replaced traditional adhesive false eyelashes and become the mainstream product in the market due to their advantages such as no need for glue, convenient wear, and no irritation to the skin around the eyes. The core component of magnetic false eyelashes is a sheet magnet, the performance of which directly determines the stability, comfort, and lifespan of the false eyelashes. Therefore, researchers in related fields have conducted extensive research on the thinness, flexibility, and high magnetic utilization of magnets used in false eyelashes.
[0003] In the prior art, Chinese invention patent CN113363047A discloses an ultrathin flexible magnetic sheet. This sheet uses synthetic fiber powder, magnetic powder, and a silane coupling agent as raw materials, and is formed through mixing, extrusion, and injection molding. It is then laterally oriented under a strong magnetic field and further processed by laser or wire cutting to obtain a magnetic sheet with a thickness of 0.02-0.4 mm, solving the problem of excessive thickness in traditional magnets. However, this technology has significant drawbacks: First, the magnetic powder is a single system, which is prone to corrosion in humid environments such as sweat, leading to rapid magnetic attenuation; second, the additive uses only a single silane coupling agent, making the magnetic sheet prone to cracking or even breakage after repeated bending, resulting in insufficient flexibility; third, the magnetic sheet causes a foreign body sensation when in direct contact with the skin around the eyes, leading to poor comfort during long-term wear.
[0004] Chinese invention patent CN119852052A addresses the issue of insufficient flexibility by introducing thermoplastic elastomer TPE and POE grafted toughening agent into the magnetic material. Flexible magnetic sheets are prepared through calendering, PU coating spraying, and stamping, improving the sheet's bending resistance. However, this technology still has several limitations: First, the unidirectional magnetization method results in uneven magnetic field distribution, causing localized lifting and detachment of false eyelashes during adsorption; second, magnetic powder tends to agglomerate in the matrix, affecting magnetic stability; third, the surface-sprayed PU coating has poor breathability, leading to stuffiness and discomfort around the eyes with prolonged wear, and its insufficient sweat resistance makes it prone to peeling off after being soaked in sweat.
[0005] Chinese invention patent CN120108883A discloses a composite permanent magnet material, which uses a mixture of pre-modified ferrite magnetic powder and neodymium iron boron magnetic powder to produce a non-magnetic magnetic eyelash strut through a process of preparing a magnetic colloid and curing it, further improving the flexibility of the magnet. However, this technology also has significant drawbacks: First, the colloid curing process has a long production cycle and low processing efficiency, making it difficult to meet the needs of large-scale production; second, the magnetic powder is modified by coating with a coupling agent, which only slightly improves its resistance to sweat corrosion.
[0006] Based on the above, existing magnetic materials and manufacturing processes for false eyelashes generally suffer from problems such as easy agglomeration of magnetic powder, uneven magnetic field distribution, and poor flexibility and sweat resistance, making it difficult to meet the comprehensive requirements of magnetic false eyelashes for high magnetic performance, excellent comfort, and safety. Therefore, how to obtain a sheet magnet for false eyelashes that combines high magnetic utilization, excellent bending resistance, sweat resistance, and biocompatibility, and its manufacturing method, has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0007] The purpose of this invention is to solve the problems of magnetic powder agglomeration and the difficulty in achieving both toughness and sweat resistance in existing false eyelash magnets. By combining ultrasonic dispersion, bidirectional magnetic field injection molding, and bio-based coating modification processes through the synergistic effect of specific component raw materials, the aforementioned problems in the prior art are resolved.
[0008] This invention is achieved through the following technical solution: This invention provides a sheet magnet for false eyelashes, the raw materials of which, by mass percentage, include 90%-99% composite neodymium iron boron magnetic powder and the balance being adhesive. The composite neodymium iron boron magnetic powder includes 70-80% core-shell structured neodymium iron boron powder, 15-22% polyamide fiber powder and the balance being functional additives. The adhesive includes 35-45% SEBS, 15-25% PP and 30-40% naphthenic oil.
[0009] Preferably, the core-shell structured NdFeB powder uses NdFeB with a particle size of 200-300 mesh as the core material, and coats the surface of the core material with a silica and bio-based polyester composite layer with a thickness of about 5-10 nm as the shell material, which can enhance corrosion resistance and dispersibility.
[0010] Preferably, the specific preparation method of core-shell structured NdFeB powder includes the following steps: (1) Magnetic particle pretreatment: Select neodymium iron boron powder with a particle size of 200-300 mesh, add a 5% dilute hydrochloric acid solution, ultrasonically clean for 10 minutes to remove any possible oxide layer on the surface, then rinse with deionized water until neutral, place in an 80℃ oven and dry for 2 hours to obtain clean neodymium iron boron magnetic powder core material.
[0011] (2) SiO2 shell coating treatment: Neodymium iron boron magnetic powder cores were added to an ethanol-water mixture with a volume ratio of 3:1 and ultrasonically dispersed for 30 min to form a magnetic powder suspension with a solid content of approximately 10%. Tetraethyl orthosilicate (TEOS) was then added dropwise to the magnetic powder suspension, with the mass ratio of TEOS to magnetic powder in the suspension controlled at 1:20. Ammonia was added dropwise to adjust the pH to 9-10, and the mixture was stirred at 30°C for 2 h to form a dense SiO2 shell on the surface of the magnetic powder. After the reaction was completed, the mixture was centrifuged, and the separated SiO2 shell magnetic powder was washed multiple times with ethanol and dried at 80°C for 3 h to obtain SiO2 shell magnetic powder.
[0012] (3) Bio-based polyester shell coating treatment: Bio-based polybutylene succinate (PBS) was selected as the coating polyester. SiO2 shell magnetic powder was added to an acetone solution of PBS with a mass concentration of about 8% and ultrasonically dispersed for 10-30 min. Then, it was stirred at 50±5℃ to allow the solvent to evaporate, so that PBS could be uniformly coated on the surface of the SiO2 shell to form a bio-based polyester layer with a thickness of 2-3 nm. Finally, it was placed in a vacuum oven and dried at 60±10℃ for 3-5 h to obtain core-shell structured NdFeB powder. In the specific embodiments, the core-shell structured NdFeB powder used was obtained by this preparation process.
[0013] Preferably, the polyamide fiber powder is a polyamide fiber powder with a particle size of 50-150μm, and preferably has a number average molecular weight Mn of 15000-30000. Specifically, bio-based PA56 can be selected, which is polypentanediamine adipate polymerized from bio-based pentanediamine and petroleum-based adipic acid, which has the effect of improving biocompatibility.
[0014] Preferably, based on the total mass of the sheet magnets for false eyelashes, the remaining functional additives include 3-5% composite toughening agent, 2-4% silane coupling agent and 0.5-1% sweat-resistant dispersant.
[0015] Furthermore, the composite toughening agent includes thermoplastic elastomer (TPE) and polylactic acid-based bio-toughening agent in a mass ratio of 1:(1-1.5), which can balance toughness and biosafety.
[0016] The particle size of TPE is 80-200μm, and the number average molecular weight Mn is 80000-150000.
[0017] Polylactic acid-based bio-toughening agents can specifically include polylactic acid-caprolactone copolymer (PLA-PCL), polylactic acid-polyethylene glycol block copolymer (PLA-PEG), polylactic acid-polyurethane copolymer (PLA-PU), etc. Those skilled in the art can also choose other equivalent substances to replace them according to actual needs.
[0018] Furthermore, existing silane coupling agents such as KH560 can be selected to improve the interfacial bonding between magnetic powder and the matrix.
[0019] Furthermore, the sweat-resistant dispersant is a fatty acid amide derivative to prevent magnetic attenuation caused by sweat. Specific fatty acid amide derivatives may include oleamide polyoxyethylene ether, erucamide propyl betaine, stearamide ethyl imidazoline, etc., but more preferably oleamide polyoxyethylene ether at an addition amount of 0.8 wt%.
[0020] The method for preparing the above-mentioned sheet magnet for false eyelashes provided by the present invention includes the following steps: (1) Mix the core-shell structured NdFeB powder, polyamide fiber powder, composite toughening agent, silane coupling agent, sweat-resistant dispersant and adhesive liquid in the composite NdFeB magnetic powder raw material, put them into an ultrasonic disperser, and disperse them at 300W power for 15-20min to achieve uniform dispersion of magnetic powder and avoid agglomeration, and obtain a premix.
[0021] (2) Place the premixed material in a mixer and mix it at 180-190℃ for 20-30 minutes. Then extrude and granulate to reduce the influence of high temperature on magnetic properties and obtain the mixed granules.
[0022] (3) The granules are put into an injection mold with an in-mold cutter for injection molding. During injection molding, a composite magnetic field of 1.0-1.5T in the transverse direction and 0.6-0.9T in the longitudinal direction is applied to achieve uniform magnetic field orientation and more balanced adsorption force. During the injection molding and holding pressure stage, the in-mold cutter is used to directly cut the granules into sheets with a thickness of 0.05-0.2mm.
[0023] (4) The injection-molded and cut sheet is placed at 60-80℃ for magnetization, and the magnetic field strength is 1.1-1.5T to avoid the magnetic properties from decaying due to high temperature, and a magnetized sheet is obtained.
[0024] (5) The surface of the magnetized sheet is activated by plasma to improve the adhesion of the coating; then it is immersed in bio-based silicone coating liquid and dried at 80°C for 10 min to form a coating with a thickness of 1-2 μm, which can improve both sweat resistance and breathability.
[0025] The bio-based silicone coating liquid includes 40-55wt% bio-based silicone resin, 0.2-0.5wt% hydrophilic modifier, 2-4wt% crosslinking agent, 35-50wt% environmentally friendly solvent, and 0.1-0.3wt% auxiliary antibacterial agent.
[0026] For example, the following raw materials can be used by weight percentage: 48% bio-based silicone resin synthesized from bamboo fiber extracted silicon source, 0.3% polyethylene glycol modified silicone oil with a molecular weight of 2000, 3% aminosilane coupling agent KH550, 47.7% ethanol-water mixed solution with a volume ratio of 2:1, and 1% chitosan quaternary ammonium salt. The bio-based silicone coating liquid used in subsequent specific embodiments adopts this raw material formula.
[0027] The preparation method of bio-based organosilicon coating liquid includes the following steps: First, add the bio-based silicone resin to an environmentally friendly solvent and stir at 300 rpm for 30 minutes at room temperature to form a uniform resin solution. Then, add a hydrophilic modifier and an auxiliary antibacterial agent to the resin solution and disperse it in an ultrasonic bath at 300W for 15 minutes to ensure that the hydrophilic groups are evenly distributed in the resin molecular chain. Next, slowly add a crosslinking agent. After the addition is complete, raise the temperature to 40°C or above and continue stirring for 1 hour to allow the crosslinking agent to fully react with the resin. Finally, let the mixed solution stand for 2 hours to remove bubbles and obtain a clear and transparent bio-based silicone coating liquid.
[0028] This bio-based silicone coating liquid can be cured at a low temperature of around 80℃ without causing the magnetic properties of the magnetic sheet to decay. The pore size of the coating formed after curing is 50-100nm, which is both breathable and sweat-resistant. There is no obvious peeling after soaking in artificial sweat for 7 days.
[0029] The technical solution of the present invention has the following beneficial effects: (1) In this invention, the structure and performance of the magnetic powder are improved. The core-shell structure neodymium iron boron powder is coated with a double layer of silicon dioxide and bio-based polyester, which can avoid the agglomeration of magnetic powder in the matrix and make the dispersion uniformity reach more than 95%. It can also isolate the erosion of electrolytes in sweat. After soaking in artificial sweat at 37°C for 7 days, the magnetic attenuation rate is ≤1%, which is far better than the attenuation rate of existing false eyelash magnets. This shows that the sheet magnet for false eyelashes and its preparation scheme provided by this invention can significantly extend the service life of false eyelashes.
[0030] (2) The present invention uses a composite toughening system of thermoplastic elastomer and polylactic acid-based bio-toughening agent, which can form an interpenetrating network structure with polyamide fiber powder, which significantly improves the bending resistance of sheet magnets and increases the elongation at break of the magnetic sheet by several times. After bending, there are no cracks or deformations.
[0031] (3) The present invention applies a composite magnetic field in both the transverse and longitudinal directions during the injection molding process, which can make the magnetic domains uniformly oriented in both directions and reduce the deviation of the magnetic adsorption force distribution. After wearing for a long time, the curling rate of false eyelashes is significantly reduced, which can solve the problem of local curling and falling off that is easy to occur in existing false eyelash magnetic sheets.
[0032] (4) The polyamide fiber powder is made of biocompatible polyamide fiber powder and combined with the bio-based silicone coating made later, which can make the false eyelash sheet magnet have good biocompatibility and high breathability. Long-term wear can reduce or even avoid the risk of stuffiness and skin irritation.
[0033] (5) The present invention adopts an in-mold integrated molding and cutting process, which is convenient and can improve the utilization rate of materials, shorten the production cycle, reduce production costs, and meet the needs of large-scale mass production. Detailed Implementation
[0034] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, they are performed according to conventional conditions or conditions recommended by the manufacturer; where the manufacturers of the instruments, equipment, reagents, or raw materials used are not specified, they are all conventional products that can be purchased commercially.
[0035] Example 1 The raw materials used in this embodiment are as follows: ① Core-shell structured neodymium iron boron powder; ② Polyamide fiber powder: Bio-based PA56 fiber powder with a particle size in the range of 80-100μm and a number average molecular weight Mn of about 23,000; ③ Composite toughening agent: styrene-ethylene-butene-styrene block copolymer (SEBS), with a particle size in the range of 120-130μm and Mn of about 110,000; polylactic acid-caprolactone copolymer (PLA-PCL), and the mass ratio of SEBS to PLA-PCL is 1:1; ④Silane coupling agent KH560; ⑤ Antiperspirant: Oleamide polyoxyethylene ether; ⑥ Bio-based silicone coating liquid.
[0036] The process for preparing the sheet magnet for false eyelashes in this embodiment is as follows: (1) By mass percentage, take 73% core-shell structured NdFeB powder, 17% bio-based PA56 fiber powder, 5% composite toughening agent, 2% silane coupling agent KH560, 1% oleamide polyoxyethylene ether and 2% adhesive, mix and then ultrasonically disperse at 300W for 20min. (2) Place the mixed material in a 185°C kneader for 25 min, then extrude and granulate. (3) The granulated material is put into a mold with an in-mold cutter for injection molding. A composite magnetic field of 1.2T in the transverse direction and 0.8T in the longitudinal direction is applied during injection molding. During the holding pressure stage, it is cut into sheets with a thickness of 0.1mm. (4) Magnetize the sheet at 70°C with a magnetic field strength of 1.2T; (5) The magnetized sheet is activated by plasma and impregnated with bio-based silicone coating liquid. It is then dried at 80°C for 10 min to form a bio-based silicone coating, thus obtaining a sheet magnet for false eyelashes.
[0037] Example 2 The difference between this embodiment and Embodiment 1 is that the Mn content of the bio-based PA56 powder is 15000.
[0038] Example 3 The difference between this embodiment and Embodiment 1 is that the ratio of the composite toughening agent is SEBS:PLA-PCL=1:1.5.
[0039] Example 4 The difference between this embodiment and Example 1 is that the content of polyethylene glycol modified silicone oil in the bio-based silicone coating liquid is 0.5%, while the relative content of the other components remains unchanged.
[0040] Comparative Example 1 The difference between this comparative example and Example 1 is that: NdFeB magnetic powder raw material without composite coating is used instead of core-shell structure NdFeB powder.
[0041] Comparative Example 2 The difference between this comparative example and Example 1 is that a single-component SEBS is used as the composite toughening agent.
[0042] Comparative Example 3 The difference between this comparative example and Example 1 is that only a transverse magnetic field of 1.2T is applied during injection molding.
[0043] Comparative Example 4 The difference between this comparative example and Example 1 is that a PU coating as described in the background art is used instead of a bio-based silicone coating liquid.
[0044] Comparative Example 5 The difference between this comparative example and Example 1 is that the raw materials for preparing the sheet magnets only include 20wt% polyamide fiber powder, 75wt% neodymium iron boron magnetic powder and 5wt% silane coupling agent; only a transverse magnetic field of 1.2T is applied during injection molding; and no coating treatment is applied after magnetization.
[0045] Comparative Example 6 The difference between this comparative example and Example 1 is that the raw materials for preparing the sheet magnet include only 3wt% TPE, 85wt% NdFeB magnetic powder, 1wt% titanate coupling agent, 1wt% toughening agent POE and 10wt% copolymer polypropylene. It is calendered as described in the background art, magnetized at 800Gs, and then coated with PU.
[0046] Test case Samples: Examples 1-4, Comparative Example 6 Different samples were taken from each sample, and the cross-section of the sheet was observed. The proportion of magnetic powder dispersion area was statistically analyzed to characterize the uniformity of magnetic powder dispersion. Each sample was subjected to a 180° reciprocating bend using a bending tester, and the number of bends at breakage was recorded. Each sample sheet was also immersed in artificial sweat at 37°C for 7 days, and the rate of change in magnetic flux before and after immersion was tested to characterize the magnetic attenuation rate. Each sample was also subjected to simulated eye contact for 8 hours, and the proportion of warped edges in 100 repeated tests for each sample was statistically analyzed; this was the warping rate. Finally, the ratio of the mass of the qualified product after molding to the total mass of the raw materials was calculated to characterize the material utilization rate.
[0047] The test data from the above experiments are summarized in Table 1 below: Table 1. Material property test results of different samples
[0048] The above experiments and the test data obtained show that: Examples 1-4 all utilize the sheet magnet for false eyelashes and its preparation method proposed in this invention. Compared to Comparative Examples 1-6, the sheet magnet samples for false eyelashes in Examples 1-4 exhibit significantly better uniformity of magnetic powder dispersion, bending resistance, sweat resistance, and wearing stability. In Comparative Example 1, the lack of core-shell coating resulted in severe magnetic powder agglomeration, leading to a significant decrease in bending resistance and sweat resistance, demonstrating that the core-shell structure is a key technical feature for improving magnetic powder dispersion and corrosion resistance. Comparative Example 2 uses a single toughening agent, but the bending resistance is only 600 times, indicating that the synergistic effect of the composite toughening system can significantly improve toughness. Comparative Example 3 uses a unidirectional magnetic field, with a curling rate as high as 12%, proving that bidirectional magnetic field orientation can optimize the distribution of adsorption force and improve wearing stability. Comparative Example 4 uses a PU coating, which has poor breathability, proving that bio-based silicone coatings are more suitable for eye contact scenarios. Comparative Examples 5-6 use existing raw material formulations and preparation methods for false eyelash magnet sheets, and all performance aspects are significantly inferior to Examples 1-4 of this invention, demonstrating that the technical solution of this invention has outstanding substantive features and significant progress.
[0049] This demonstrates that the sheet magnet for false eyelashes produced by the present invention, through synergistic improvement of raw material composition and process, far surpasses existing false eyelash magnet sheets in terms of magnetic powder dispersibility, flexibility, sweat resistance, biocompatibility, and processing efficiency, and has significant market application value.
[0050] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A sheet magnet for false eyelashes, characterized in that, By mass percentage, the raw materials consist of 90%-99% composite NdFeB magnetic powder and the remainder being adhesive; the composite NdFeB magnetic powder includes core-shell structured NdFeB powder, polyamide fiber powder, and functional additives, including composite toughening agents, silane coupling agents, and sweat-resistant dispersants; the adhesive includes SEBS, PP, and naphthenic oil; The composite toughening agent comprises a thermoplastic elastomer and a polylactic acid-based bio-toughening agent in a mass ratio of 1:(1-1.5); The core-shell structured NdFeB powder uses NdFeB as the core material and a silica and bio-based polyester composite layer coated on the surface of the core material as the shell material. The preparation method of the core-shell structured NdFeB powder includes the following steps: A1 Magnetic Powder Pretreatment: Take neodymium iron boron, first pickle it, then rinse it with deionized water until neutral, and dry it to obtain clean neodymium iron boron magnetic powder core material; A2 SiO2 shell coating treatment: Neodymium iron boron magnetic powder core material is dispersed in a solvent to prepare a magnetic powder suspension; then tetraethyl orthosilicate is added dropwise and the pH value is adjusted to alkaline. The mixture is stirred and reacted, then separated, washed and dried to obtain SiO2 shell magnetic powder. A3 Bio-based polyester shell coating treatment: First, bio-based polybutylene succinate is added to a volatile solvent, then SiO2 shell magnetic powder is added and ultrasonically dispersed; then heated and stirred to form a bio-based polyester layer on the surface of SiO2 shell magnetic powder, and dried to obtain core-shell structured NdFeB powder.
2. The sheet magnet for false eyelashes according to claim 1, characterized in that, The particle size of neodymium iron boron is 200-300 mesh; the total thickness of the SiO2 shell and the bio-based polyester shell is 5-10 nm, and the thickness of the bio-based polyester layer is 2-3 nm.
3. The sheet magnet for false eyelashes according to claim 1, characterized in that, The particle size of the polyamide fiber powder is 50-150μm, and the number average molecular weight Mn is 15000-30000.
4. The sheet magnet for false eyelashes according to claim 1, characterized in that, The particle size of thermoplastic elastomers is 80-200 μm, and the number average molecular weight Mn is 80,000-150,000.
5. The sheet magnet for false eyelashes according to claim 1, characterized in that, The polylactic acid-based bio-toughening agent is selected from one or more of polylactic acid-caprolactone copolymer, polylactic acid-polyethylene glycol block copolymer, and polylactic acid-polyurethane copolymer.
6. The sheet magnet for false eyelashes according to claim 1, characterized in that, The antiperspirant is selected from one or more of oleamide polyoxyethylene ether, erucamide propyl betaine, and stearamide ethyl imidazoline.
7. A method for preparing a sheet magnet for false eyelashes as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1 Take core-shell structured neodymium iron boron powder, polyamide fiber powder, composite toughening agent, silane coupling agent, sweat-resistant dispersant and adhesive solution respectively, mix them, and ultrasonically disperse them to obtain a premix; S2 The premixed material is kneaded at 180-190℃ for 20-30 minutes, then extruded and granulated to obtain kneaded granules; S3 involves injection molding the internally mixed granules, and during injection molding, a composite magnetic field of 1.0-1.5T in the transverse direction and 0.6-0.9T in the longitudinal direction is applied. After injection molding, the granules are sliced to obtain sheets with a thickness of 0.05-0.2mm. S4 The sheet is magnetized at 60-80℃ with a magnetic field strength of 1.1-1.5T to obtain a magnetized sheet; S5 uses plasma to activate the surface of the magnetized sheet, then immerses it in a bio-based silicone coating liquid, heats and dries it to form a coating with a thickness of 1-2 μm, thus obtaining the sheet magnet for the false eyelashes.
8. The method for preparing a sheet magnet for false eyelashes according to claim 7, characterized in that, In step S5, the bio-based silicone coating liquid comprises, by mass percentage, 40-55 wt% bio-based silicone resin, 0.2-0.5 wt% hydrophilic modifier, 2-4 wt% crosslinking agent, 35-50 wt% environmentally friendly solvent, and 0.1-0.3 wt% auxiliary antibacterial agent.
Citation Information
Patent Citations
Ultrathin flexible magnetic sheet and application
CN113363047A
Flexible magnetic sheet for false eyelashes and preparation process thereof
CN119852052A
Composite permanent magnet material and non-magnetic block magnetic attraction false eyelash
CN120108883A
Preparation method of immune amorphous magnetic beads for cell separation
CN118389412A
Lipase immobilization method and application
CN120699957A